2014
DOI: 10.4049/jimmunol.1303424
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for Human Caspase-4 in Endotoxin Sensitivity

Abstract: Response to endotoxins is an important part of the organismal reaction to gram-negative bacteria, and plays a critical role in sepsis and septic shock, as well as other conditions such as metabolic endotoxemia. Humans are generally more sensitive to endotoxins when compared to experimental animals such as mouse. Inflammatory caspases mediate endotoxin-induced interelukin-1β (IL-1β) secretion and lethality in mouse, and caspase-4 is an inflammatory caspase that is found in the human, and not mouse, genome. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 53 publications
3
93
0
Order By: Relevance
“…54). Nevertheless, to date, only a few studies reported the potential involvement of caspase-4 in the activation of the inflammasomes (30,55). Our results indicate that caspase-4 is indeed required for the priming of the inflammasome, as the absence of this caspase resulted in a severe impairment of pro-IL-1␤ synthesis.…”
Section: Discussionmentioning
confidence: 55%
“…54). Nevertheless, to date, only a few studies reported the potential involvement of caspase-4 in the activation of the inflammasomes (30,55). Our results indicate that caspase-4 is indeed required for the priming of the inflammasome, as the absence of this caspase resulted in a severe impairment of pro-IL-1␤ synthesis.…”
Section: Discussionmentioning
confidence: 55%
“…Consumption of high-fat diet has been shown to induce an increase in the level of blood LPS in mice and humans (and likely endogenous oxidatively modified lipids as well), leading to metabolic endotoxemia, and insulin resistance (81)(82)(83)(84). Since caspase-4 is expressed in peripheral immune cells such as macrophages (27), it is tempting to speculate that caspase-4 in part mediates such response to peripheral endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported on the development and characterization of a novel transgenic mouse expressing human caspase-4 from its native regulatory elements. In these studies, we observed a crucial role for caspase-4 in not only initiating inflammatory cell death but also priming the Nlrp3 inflammasome and caspase-1 activation (27). Caspase-4 is an intracellular receptor for LPS leading to an induction of pyroptosis (28) by cleaving gusdermin D (29,30), and activates the non-canonical Nlrp3 inflammasome leading to activation of caspase-1 and secretion of IL-1b and IL-18 (31)(32).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The limited literature on these human caspases suggests their activation by intracellular pathogens, and proposes functions in triggering IL-18 production and pyroptosis in infected epithelial cells [21]. Studies from a transgenic mouse expressing human caspase-4 implicated this caspase, like murine caspase-11, as an important mediator of endotoxin sensitivity [22]. The evolution of multiple inflammatory caspases capable of pyroptosis initiation highlights the importance of this process as an anti-microbial defence strategy.…”
Section: Pyroptosis Initiation By Other Inflammatory Caspasesmentioning
confidence: 99%